2021
DOI: 10.21608/ejabf.2021.165911
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationship and Fulton’s Condition Factor of Macrobrachium nipponense (De Haan, 1849) in Siah Darvishan River, Iran

Abstract: 1849), and known to be omnivorous (New et al., 2010). Spawning occurs in spring and summer when males appear with a hard shell and females with a soft one mate (Wakefield, 2015). The temperature has an important influence on reproduction. Morphologically, there are differences between males and females. Mature males are larger than females (Bacheler, 2013). M.nipponense was first observed in AnzaliLagoon in 2006, and later on spread in northern Iran's water basins (Coad, 2016). Prawn and shrimp of the genus Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…Values obtained for condition factor showed that both sexes of S. erythrophthalmus were in good condition. A particular seasonal trend was observed, the best condition factor for males and females was noticed during summer 6 . However, the researcher 13 reported that the best condition factors for males and females of S. erythrophthalmus were during autumn.…”
Section: Condition Factormentioning
confidence: 85%
See 1 more Smart Citation
“…Values obtained for condition factor showed that both sexes of S. erythrophthalmus were in good condition. A particular seasonal trend was observed, the best condition factor for males and females was noticed during summer 6 . However, the researcher 13 reported that the best condition factors for males and females of S. erythrophthalmus were during autumn.…”
Section: Condition Factormentioning
confidence: 85%
“…Understanding length-weight relationships in aquatic organisms such as fish are crucial to fishery management 6 . Condition factor for fish has also been widely used as an index of their growth and feeding intensity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The CCA results clearly separated all sites based on water quality. (Aminisarteshnizi, 2021). This species belongs to the phylum of Arthropoda (Order: Decapoda; Family: Palaemonidae (De Haan, 1849).…”
Section: Multi Variations Analysismentioning
confidence: 99%
“…The Anzali Lagoon is located on the Southern Coast of the Caspian Sea. The Anzali Lagoon is a large, shallow, eutrophic freshwater wetland, marshes and seasonally-flooded grasslands between land and sea ecosystems and between freshwater and brackish ecosystems form a special ecotone embracing a unique blend of plant and animal communities 1 .…”
Section: Introductionmentioning
confidence: 99%